Holographic collisions in non-conformal theories - Attems, M; Casalderrey-Solana, J; Mateos, D; Santos-Oliván, D; Sopuerta, C; Triana, M; Zilhão, M (Springer Verlag, 2017)
We numerically simulate gravitational shock wave collisions in a holographic model dual to a non-conformal four-dimensional gauge theory. We find two novel effects associated to the non-zero bulk viscosity of the resulting plasma. First, the hydrodynamization time increases. Second, if the bulk viscosity is large enough then the plasma becomes well described by hydrodynamics before the energy density and the average pressure begin to obey the equilibrium equation of state. We discuss implications for the quark-gluon plasma created in heavy ion collision experiments.